تطبيق المناهج الالكترونية من وجهة نظر معلمي بعض المدارس الابتدائية دراسة ميدانية الاغواط - رودوسي صورية; حرابي نعيمة; بن يحي عطالله (My University, 2023)
The studyaimed to reveal the reality of the application of electronic curricula from the point of view of teachers of someprimaryschools in Laghouat, to identify the level of application of electronic curricula and to detectdifferences in the extent of their application according to some variables: gender (male-female), age, schoolsubject, number of years of teachingexperience. Proficiency in the use of electronictouls. The studysampleconsisted of (95) male and femaleteachers, and the descriptive relationalapproachwasadopted. To achieve the objectives of the study, the researchersrelied on a questionnaire, "The Reality of ApplyingElectronic Curricula". The statisticaltreatmentwasdoneusing the statistical package for social sciences (spss), where the results of the studywere as follows: - There is a lowlevel point of viewamong the teachers of someprimaryschools. - There are no statisticallysignificantdifferences in the application of electronic curricula according to gender (male-female). - There are no statisticallysignificantdifferences in the reality of applyingelectronic curricula according to age. - There are no statisticallysignificantdifferences in the reality of applyingelectronic curricula according to the number of years of teachingexperience. Key words : Electronic curricu